Identification of chromosome 3q28 and ALPK1 as susceptibility loci for chronic kidney disease in Japanese individuals by a genome-wide association study. Issue 6 (28th March 2013) - Yamada, Yoshiji; Nishida, Tamotsu; Ichihara, Sahoko; Kato, Kimihiko; Fujimaki, Tetsuo; Oguri, Mitsutoshi; Horibe, Hideki; Yoshida, Tetsuro; Watanabe, Sachiro; Satoh, Kei; Aoyagi, Yukitoshi; Fukuda, Michio; et al.
Abstract : Background: Although genome-wide association studies (GWASs) have implicated several genes in the predisposition to chronic kidney disease (CKD) in Caucasian or African American populations, the genes that confer susceptibility to CKD in Asian populations remain to be identified definitively. We performed a GWAS to identify genetic variants that confer susceptibility to CKD in Japanese individuals. Methods: 3851 Japanese individuals from three independent subject panels were examined. Subject panels A, B, and C comprised 252, 910, and 190 individuals with CKD and 249, 838, and 1412 controls, respectively. A GWAS for CKD was performed in subject panel A. Results: Five single nucleotide polymorphisms (SNPs) at chromosome 3q28, ALPK1, FAM78B, and UMODL1 were significantly (false discovery rate<0.05) associated with CKD by the GWAS. The relation of these five SNPs and of an additional 22 SNPs at these loci to CKD was examined in subject panel B, revealing that rs9846911 at 3q28 was significantly associated with CKD in all individuals and that rs2074381 and rs2074380 in ALPK1 were associated with CKD in individuals with diabetes mellitus. These three SNPs were further examined in subject panel C, revealing that rs2074381 and rs2074380 were significantly associated with CKD. For subject panels B and C combined, rs9846911 was significantly associated with CKD in all individuals and rs2074381 and rs2074380 were associated with CKD in diabetic individuals. Conclusions: Chromosome 3q28 may be a susceptibility locus for CKD in Japanese individuals, and ALPK1 may be a susceptibility gene for CKD in such individuals with diabetes mellitus.